FAKTOR-FAKTOR YANG MEMPENGARUI KEMISKINAN DI PROPINSI KEPULAUAN RIAU - Raymond, Raymond (EDUTECH CONSULTANT, 2017)
This study examines the factors affecting poverty in Riau Islands Province for 2010-2015 period. The dependent variable used in this research is the number of poor people, while the independent variables are life expectancy, school participation rate, and population. Based on the results of the test, life expectancy, school participation rate, and population statistically proved significant effect on the number of poor people in Riau Islands Province.